2011
DOI: 10.1103/physrevb.84.064421
|View full text |Cite
|
Sign up to set email alerts
|

Spin-singlet trimer state induced by competing orbital order in triangular-lattice BaV10O15

Abstract: Local spin and orbital textures are investigated by 51 V NMR measurements on a triangular-lattice compound BaV 10 O 15 with orbital degrees of freedom and itinerant electrons. The Knight shift shows the spin-singlet V trimer formation in a itinerant phase above the semiconductor-insulator transition temperature T SI = 140 K. Below T SI , the observation of the asymmetric electric hyperfine coupling tensor agrees with the orbital order giving direct d-d bonds of the trimer. The remaining paramagnetic spins on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The method can be applied in the spin-singlet state. 27 For 51 V nuclear spins, I = 7/2, electric quadrupole interactions under the electric field gradient (EFG) split NMR spectra with an interval frequency δν. δν consists of the on-site d orbital and the outer ligand terms: δν = δν on + δν out , where the components of δν on are expressed by…”
mentioning
confidence: 99%
“…The method can be applied in the spin-singlet state. 27 For 51 V nuclear spins, I = 7/2, electric quadrupole interactions under the electric field gradient (EFG) split NMR spectra with an interval frequency δν. δν consists of the on-site d orbital and the outer ligand terms: δν = δν on + δν out , where the components of δν on are expressed by…”
mentioning
confidence: 99%
“…Namely, only I (0k0) /I (050) can be obtained in the calculation. On the other hand, the absolute intensities at different Q positions are difficult to compare experimentally because of the different scattering angles, 29 30 The orbital occupancies can also be discussed in the LDA calculation from the splitting of the density of the state (DOS). For example, quite large splittings of DOS are observed for the d xy and d yz states in the V2B site, and the lower states of them are occupied, whereas the higher states are unoccupied [ Fig.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 In the insulating phase of BaV 10 O 15 , V 2+ and V 3+ charge ordering is characterized by localized t 2g orbitals of d 3 and d 2 site with ferromagnetic coupling between them in the trimer, [13][14][15] which is the case contrary to the spin singlet trimers in LiV 3+ O 2 . The Raman studies previously reported on the presence of randomly oriented trimers with decreasing temperature below 220 K. 16 In addition, the splitting of V nuclear magnetic resonance (NMR) spectra indicated the symmetry lowering and no structural transition below 220 K. 17 Further from the NMR and X-ray diffraction measurements, the phase diagram of BaV 10 O 15 has shown the high-temperature phase (300 K -220 K), the intermediate-temperature phase (220 K -130 K), and the low-temperature phase (below 130 K). 17 Although the structural, transport, and optical properties are studied for BaV 10 O 15 including the electronic properties only at 75 and 300 K, [11][12][13] the electronic properties across the intermediate-temperature phase have not yet been studied.…”
Section: Introductionmentioning
confidence: 97%
“…The Raman studies previously reported on the presence of randomly oriented trimers with decreasing temperature below 220 K. 16 In addition, the splitting of V nuclear magnetic resonance (NMR) spectra indicated the symmetry lowering and no structural transition below 220 K. 17 Further from the NMR and X-ray diffraction measurements, the phase diagram of BaV 10 O 15 has shown the high-temperature phase (300 K -220 K), the intermediate-temperature phase (220 K -130 K), and the low-temperature phase (below 130 K). 17 Although the structural, transport, and optical properties are studied for BaV 10 O 15 including the electronic properties only at 75 and 300 K, [11][12][13] the electronic properties across the intermediate-temperature phase have not yet been studied. In view of the complicated transport and optical properties across the intermediate-temperature phase, 11,16,17 the present work is dedicated to study the electronic properties at 180, 245, and 300 K including the insulating phase (70 K).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation